THE APPLICATION OF VISUAL SOCIAL STORY AND ROLE PLAY INTERVENTIONS TO IMPROVE SOCIAL COMMUNICATION IN ADOLESCENTS WITH AUTISM SPECTRUM DISORDER AT SLB HARAPAN BUNDA SURABAYA. - Fonda, Nicken Julian (JPI (Jurnal Pendidikan Inklusi), 2023)
Individuals with autism have barriers to social communication and need methods to improve their social communication. The application of  the intervention aims to determine the improvement of children's social communication consisting of communication skills as a basis for developing social skills with the subject being an 18-year- old woman who has a diagnosis of Autism Spectrum Disorder (ASD) who attends SLB Harapan Bunda Surabaya. Improved communication skills are obtained by visual social story method and improved social skills using role play method. The results of the application of the intervention showed that there was an improvement in the communication skills of subjects who became the basis for the development of social skills in adolescents with Autism Spectrum Disorder. Keywords: social communication, visual social stories, role play, teenagers, autism spectrum disorder.